Effect of Curing Direction on Microtensile Bond Strength of Fifth and Sixth Generation Dental Adhesives - Ali Nadaf; Majid Mousvinasab; Alireza Danesh Kazemi; Abdolrahim Davari (Tehran University of Medical Sciences, 2012)
Background and Aims: Composite restorative materials and dental adhesives are usually cured with light sources. The light direction may influence the bond strength of dental adhesives. The aim of this study was to evaluate the effect of light direction on the microtensile bond strength of fifth and sixth generation dental adhesives.Materials and Methods: Prime & Bond NT and Clearfil SE bond were used with different light directions.Sixty human incisor teeth were divided into 4 groups (n=15). In groups A and C, Clearfil SE bond with light curing direction from buccal was used for bonding a composite resin to dentin. In groups B and D, Prime & Bond NT with light curing direction from composite was used. After thermocycling the specimens were subjected to tensile force until debonding occurred and values for microtensile bond strength were recorded. The data were analyzed using two-way ANOVA and Tukey post hoc test.Results: The findings showed that the bond strength of Clearfil SE bond was significantly higher than that of Prime&Bond NT (P<0.001). There was no significant difference between light curing directions (P=0.132).Conclusion: Light curing direction did not have significant effect on the bond strength. Sixth generation adhesives was more successful than fifth generation in terms of bond strength to dentin.